The Impostor Phenomenon Among Nursing Students and Nurses: A Scoping Review - Peng, Ying; Xiao, Shao-Wen; Tu, Hui; Xiong, Xiao-Yun; Ma, Zhao-Jia; Xu, Wen-Jun; Cheng, Ting (Frontiers in Psychology, 2022)
The impostor phenomenon (IP) refers to a false internal experience of low intelligence or ability that is associated with anxiety, depression, psychological distress and burnout. The emotions associated with the IP affect not only personal mental health but also patient care. To address this issue, we need to completely understand the prevalence of and factors related to the IP and ways to resolve/overcome IP feelings. The aim of this scoping review was to identify the existing evidence regarding the IP among nursing students and nurses and determine gaps that can be addressed in future research. We conducted our study based on the scoping review methodological framework proposed by Arksey and O'Malley and advanced by Levac et al. After searching the Embase, PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Cochrane Library, Web of Science and ProQuest databases, we identified 11 studies for inclusion in this review. We found that while the IP exists in nursing students and nurses, clinical nurse specialist students and final-year nursing students are at significant risk of impostor behaviour. We also found that research in the nursing field has focused on the prevalence of and factors related to the IP, but few studies have addressed ways to resolve/overcome IP feelings. Thus, research in this area should be increased. This scoping review presents research gaps that may serve as a starting point for future work on the IP in the nursing field.